2021
DOI: 10.1002/ccd.29464
|View full text |Cite
|
Sign up to set email alerts
|

Tricuspid regurgitation after transcatheter mitral valve repair: Clinical course and impact on outcome

Abstract: Objectives: The aim of this study was to determine the course of tricuspid regurgitation (TR) after transcatheter mitral valve repair (TMVR), identify predictors for severe TR after TMVR and determine the association of severe TR after TMVR with outcome.Background: TR is often present in patients with symptomatic mitral regurgitation (MR) and is associated with increased morbidity and mortality. The clinical course of TR after TMVR has not been clearly determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…However, RV function as assessed by tricuspid annular plane systolic excursion (TAPSE) was similar in both groups. Disagreeing with our data, Meijerink et al described TR regression as mainly occurring in patients with RV dysfunction at baseline [19].…”
Section: Discussionsupporting
confidence: 82%
“…However, RV function as assessed by tricuspid annular plane systolic excursion (TAPSE) was similar in both groups. Disagreeing with our data, Meijerink et al described TR regression as mainly occurring in patients with RV dysfunction at baseline [19].…”
Section: Discussionsupporting
confidence: 82%
“…Right ventricular function improved in 55% of patients and deterioration of RV function was characterised by excessive mortality [23]. Tricuspid regurgitation improved in 23-35%, and persistence of TR after TMVR was associated with impaired long-term prognosis and decreased symptomatic benefit [17,31,[38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…The composite endpoint of deaths and rehospitalizations for heart failure was significantly more frequent in the presence of 4+/3+ (67.7 vs. 88.8%; log-rank p = 0.015) [13]. Similarly, Meijerink et al [14] found differences in the prognosis of patients undergoing MitraClip procedures depending on the coexisting tricuspid regurgitation. Survival of patients with severe TR after transcatheter mitral valve repair was 58% after two years compared to 82% for those with non, mild or moderate TR.…”
Section: Discussionmentioning
confidence: 88%